Efficacy and Safety of Metronidazole Monotherapy versus Vancomycin Monotherapy or Combination Therapy in Patients with Clostridium difficile Infection: A Systematic Review and Meta-Analysis - Li, Rui; Lu, Laichun; Lin, Yu; Wang, Mingxia; Liu, Xin (PLOS ONE, 2015)
Background Clostridium difficile infection (CDI) has become a global epidemiological problem for both hospitalized patients and outpatients. The most commonly used drugs to treat CDI are metronidazole and vancomycin. The aim of this study was to compare the efficacy and safety of metronidazole monotherapy with vancomycin monotherapy and combination therapy in CDI patients. Methods A comprehensive search without publication status or other restrictions was conducted. Studies comparing metronidazole monotherapy with vancomycin monotherapy or combination therapy in patients with CDI were considered eligible. Meta-analysis was performed using the Mantel-Haenszel fixed-effects model, and odds ratios (ORs) with 95% confidence intervals (95% CIs) were calculated and reported. Results Of the 1910 records identified, seventeen studies from thirteen articles (n = 2501 patients) were included. No statistically significant difference in the rate of clinical cure was found between metronidazole and vancomycin for mild CDI (OR = 0.67, 95% CI (0.45, 1.00), p = 0.05) or between either monotherapy and combination therapy for CDI (OR = 1.07, 95% CI (0.58, 1.96), p = 0.83); however, the rate of clinical cure was lower for metronidazole than for vancomycin for severe CDI (OR = 0.46, 95% CI (0.26, 0.80), p = 0.006). No statistically significant difference in the rate of CDI recurrence was found between metronidazole and vancomycin for mild CDI (OR = 0.99, 95% CI (0.40, 2.45), p = 0.98) or severe CDI (OR = 0.98, 95% CI (0.63, 1.53), p = 0.94) or between either monotherapy and combination therapy for CDI (OR = 0.91, 95% CI (0.66, 1.26), p = 0.56). In addition, there was no significant difference in the rate of adverse events (AEs) between metronidazole and vancomycin (OR = 1.18, 95% CI (0.80, 1.74), p = 0.41). In contrast, the rate of AEs was significantly lower for either monotherapy than for combination therapy (OR = 0.30, 95% CI (0.17, 0.51), p<0.0001). Conclusions Metronidazole and vancomycin are equally effective for the treatment of mild CDI, but vancomycin is superior for the treatment of severe CDI. Combination therapy is not superior to monotherapy because it appears to be associated with an increase in the rate of AEs.